Virtual Reality, Augmented Reality, and Virtual Environments: Demonstrations of Current Technologies and Future Directions. (December 2020) - Beadle, Sarah; Spain, Randall; Goldberg, Benjamin; Ebnali, Mahdi; Bailey, Shannon; Ciccone, Brendan; Wilson, Ragan; Rubensky, Summer; Carroll, Meredith; Bennett, Winston; Hu, Xueyu; Reiner, Adam; et al.
Virtual environments and immersive technologies are growing in popularity for human factors purposes. Whether it is training in a low-risk environment or using simulated environments for testing future automated vehicles, virtual environments show promise for the future of our field. The purpose of this session is to have current human factors practitioners and researchers demonstrate their immersive technologies. This is the eighth iteration of the "Me and My VE" interactive session. Presenters in this session will provide a brief introduction of their virtual reality, augmented reality, or virtual environment work before engaging with attendees in an interactive demonstration period. During this period, the presenters will each have a multimedia display of their immersive technology as well as discuss their work and development efforts. The selected demonstrations cover issues of designing immersive interfaces, military and medical training, and using simulation to better understand complex tasks. This includes a mix of government, industry, and academic-based work. Attendees will be virtually immersed in the technologies and research presented allowing for interaction with the work being done in this field.